2009
DOI: 10.1080/10599240903389508
|View full text |Cite
|
Sign up to set email alerts
|

Migrant Farmworker Field and Camp Safety and Sanitation in Eastern North Carolina

Abstract: Migrant farmworkers are exposed to numerous workplace hazards, with pesticides being a ubiquitous occupational exposure. This analysis describes farmworker experiences of field and camp safety conditions and their safety behaviors, and delineates farmworker characteristics associated with safety conditions and behaviors. Data were collected from 255 migrant farmworkers up to four times at monthly intervals during the 2007 agricultural season in eastern North Carolina. Measures assess field safety conditions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 32 publications
3
56
0
1
Order By: Relevance
“…However, these results are valid for large businesses only, because by law, employers are required to protect workers from pesticide exposure. 8 In smaller businesses, the individual workers are the ones who take the protective measures, and the decision to use the PPE depends on their knowledge, attitudes, and beliefs. 27 In a cultural context like the one existing in Mexico, some authors have referred to "Hispanic fatalism," that is, the perception that individuals have little control over whether they develop, or die from, a disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, these results are valid for large businesses only, because by law, employers are required to protect workers from pesticide exposure. 8 In smaller businesses, the individual workers are the ones who take the protective measures, and the decision to use the PPE depends on their knowledge, attitudes, and beliefs. 27 In a cultural context like the one existing in Mexico, some authors have referred to "Hispanic fatalism," that is, the perception that individuals have little control over whether they develop, or die from, a disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although compliance with the WPS training requirement has not been fully evaluated, results from studies in California, North Carolina, and Texas show the percentage of workers ever receiving pesticide training ranging from 35.2% to 76.8%. 15–18 …”
Section: Discussionmentioning
confidence: 99%
“…Mirabelli et al 13 reported changes in work hours and activities during hot conditions were associated with a lower prevalence of heat illness among workers with H-2A visas, but not among non-H-2A workers. Also, Whalley et al 30 reported that workers with H-2A visas experience better conditions and practice more safety behaviours than do workers who do not have H-2A visas. Farmworkers with H-2A visas may work for agricultural employers seeking to hire temporary agricultural workers, usually in relation to the production and/or harvesting of a crop, or for a limited time period of less than one year when an employer can show that the need for the foreign workers(s) is truly temporary 31…”
Section: Discussionmentioning
confidence: 99%